Polypyrrole-based adsorbents for Cr(VI) ions remediation from aqueous solution: a review - Marko Chigondo (Water Science and Technology, 2022)
Anthropogenic activities are principally responsible for the manifestation of toxic and carcinogenic hexavalent chromium (Cr(VI)) triggering water pollution that threatens the environment and human health. The World Health Organisation (WHO) restricts Cr(VI) ion concentration to 0.1 and 0.05 mg/L in inland surface water and drinking water, respectively. The available technologies for Cr(VI) ion removal from water were highlighted with an emphasis on the adsorption technology. Furthermore, the characteristics of several polypyrrole-based adsorbents were scrutinized including amino-containing compounds, biosorbents, graphene/graphene oxide, clay materials and many other additives with reported effective Cr(VI) ion uptake. This efficiency in Cr(VI) ions adsorption is attributed to enhanced redox properties, increased number of functional groups as well as the synergistic behaviour of the materials making up the composites. The Langmuir isotherm best described the adsorption processes with maximum adsorption capacities ranging from 3.40–961.50 mg/g. The regeneration of Cr(VI) ion-laden adsorbents was studied. Ion exchange, electrostatic attractions, complexation, chelation reactions with protonated sites and reduction were the mechanisms of adsorption. Nevertheless, there are limited details on comprehensive adsorbent regeneration studies to prolong robustness in adsorption–desorption cycles and utilization of the Cr(VI) ion-laden adsorbent in other areas of research to limit the threat of secondary pollution. HIGHLIGHTS Hexavalent chromium sources, pollution and toxicity.; Remediation through absorption technology.; Polypyrrole-based adsorbents.; Utilization of Cr(VI)-laden adsorbent waste in other areas of research.;